ARSITEKTUR CONTAINER DOCKER PADA APLIKASI EXPERT ASSIST DENGAN TEKNOLOGI NODE.JS, EXPRESS FRAMEWORK & CLOUD DATABASE NoSQL MONGODB ATLAS - Sutanto Sutanto; Waliadi Gunawan; Faeshal Faeshal (Jurnal Sistem Informasi dan Informatika (Simika), 2021)
In the world of software development, the crusial thing we must do is design the architecture. We can said the system is good if it has a good architecture too, because the system architecture will affect the performance of applications itself, from the architecture we can also read what technology is used until security aspect. The main problems that i want to solve are two things, first the problem in the process of software development which will be solve by implementing Docker container architecture & Node.JS and second problems is in society that will be solve by the Expert Assist application. In the case of software development the problems is often when developing applications the architecture is not scalable, conflicts between applications in the system, services that are still centralized, application portability issues, security optimization problems and different environments between the development and production server that will affect developer productivity, problems about not independent and robustless app, resource efficiency and the problem with blocking code that appear in server side conventional programming languages. The problem in society is the difficulty to finding a mentor who can help us to solve the problems we have, that is why Expert Assist application was made. Expert Assist is a web based online platform that will help all people in various fields to finding a mentor who is an expert in his field because not all problems can be solved by independent research or self-taught, if the problem is very complex we need someone who can help us to provide advice in order to solve our problem.